2002
DOI: 10.1021/ja026975w
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide Supported Nanopalladium Catalyst for Heck-, Suzuki-, Sonogashira-, and Stille-Type Coupling Reactions of Chloroarenes

Abstract: Layered double hydroxide and Merrifield resin supported nanopalladium(0) catalysts are prepared by an exchange of PdCl(4)(2-) followed by reduction and well characterized for the first time. The ligand-free heterogeneous layered double hydroxide supported nanopalladium (LDH-Pd(0)) catalyst using the basic LDH in place of basic ligands indeed exhibits higher activity and selectivity in the Heck olefination of electron-poor and electron-rich chloroarenes in nonaqueous ionic liquids (NAIL) over the homogeneous Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
363
1
6

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 734 publications
(378 citation statements)
references
References 37 publications
8
363
1
6
Order By: Relevance
“…The oxidation form of Pd is possibly palladium oxide, which may result from the surface oxidation of palladium nanoparticles when they are exposed to air. A similar phenomenon was also reported by others [42,43].…”
Section: Characterizationssupporting
confidence: 91%
See 2 more Smart Citations
“…The oxidation form of Pd is possibly palladium oxide, which may result from the surface oxidation of palladium nanoparticles when they are exposed to air. A similar phenomenon was also reported by others [42,43].…”
Section: Characterizationssupporting
confidence: 91%
“…The two peak components at the BEs [36,42]. The other set of peaks at 337.7 eV (Pd 3d 5/2 ) and 342.9 eV (Pd 3d 3/2 ) is ascribed to the Pd 2+ [38,43]. Calculating the integration areas of these two doublets using XPS-PEAK software, it can be estimated that the atomic ratio of Pd 0 /Pd 2+ was about 59:41.…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deposition of highly dispersed Pd supported on hydrotalcites has been executed using various synthesis methods, such as co-precipitation [18], deposition-precipitation [26], impregnation [27][28][29] or by use of Pd clusters in a polymer [30]. However, the main focus of these studies was on the hydrogenation reaction and no attention has been given on the basic function.…”
Section: Introductionmentioning
confidence: 99%
“…73,74 For example, palladium supported on calcined MgAl-LDH has been used for the one-pot synthesis of 4-methyl-2-pentanone (methyl isobutylketone) from acetone and hydrogen at an atmospheric pressure. 75 Choudary et al 76 studied Pd(0) catalysts supported on MgAl-LDHs prepared by ion-exchange with PdCl 4 2− , followed by reduction. They observed that the catalysts, used in ionic liquids, not only exhibited higher activity and selectivity than the homogeneous PdCl 2 system in the Heck olefination of electron-poor and electron-rich chloroarenes, but also showed superior activity in the C-C coupling reactions of chloroarens compared with other heterogeneous catalysts involving Pd(0) on supports such as silica, alumina or Merrifield's resin.…”
Section: Catalytic Applicationsmentioning
confidence: 99%